Money growth and social stability - Erdem Başçı; Sıdıka Başçı; Tahar Gherby (The Central European Review of Economics and Management (CEREM), 2021)
Aim: Both the Keynesian and the Fisherian channels of sovereign money growth have slowed down significantly in the decade following the Global Financial Crisis (GFC). This, together with the rise of fintech, privately issued unbacked crypto-assets tried to fill this void. These developments have revived the interest on the Central Bank Digital Currency (CBDC) idea and on potential channels for future sovereign money growth. The aim of this paper is to compare the Keynesian and Fisherian channels of sovereign money growth regarding their impact on wealth distribution and inflation. Design / Research Methods: To achieve our aim we use a simple Agent Based Model (ABM) to capture heterogeneity. In our model, the agents are heterogeneous consumers with different spending propensities but with equal initial wealth levels and with exactly same non-interest incomes over time. Conclusions / findings: We show that Keynesian (uniform) money growth channel has a softening effect on the wealth dispersion and thereby, on the downward pressure on money velocity. The model indicates that the inclusive nature of current post-Covid19 recovery plans may have a desirable impact on social stability. Yet, these plans may also be more inflationary in comparison the post-GFC policies. Originality / value of the article: This paper shows that heterogeneity of economic agents should not be ignored by policy makers and that ABM is a convenient tool to design and analyse monetary and fiscal policies under heterogeneity. Implications of the research: The implication for policy makers is that the demand deficiency associated with the fall in money velocity and the worsening of wealth dispersion may be softened by a more inclusive money growth regime, potentially with the practical use of CBDCs. Yet the extra inflationary impact of such a regime need to be kept in mind.
Keywords: D31; E4; E63; 330; Money Velocity; Money Growth; Heterogeneity; CBDC; Wealth Distribution; Sustainable Development Goals; SDG10; Inequalities; Inflation